UTERINE CERVICAL EVALUATION: DIFFICULTIES AND FACILITIES IN THE CUSTOMER SERVICE - Assis Silva Reis da Fonseca, Nayne; Conceição de Assis, Jefferson; Gomes da Silva, William; Carolina Salustino dos Santos, Maria (Health and Society, 2023)
The Pap smear is of great value in the sphere of Women’s Health, which is why a more effective and safe screening program is necessary. completion of the examination request, collection and analysis of the smear. Some obstacles still persist in carrying out the Pap smear test in Brazil, among them we can highlight the delay in delivering the result, the difficulty of accessing UBS in some isolated regions of the country, the lack of information of some women regarding the performance of the test every two years when you do not have a positive result in the last exams.